Methodical aspects of work on the qualification work of future teachers of fine arts - Bryzhata, I.H. (Pedagogy of Higher and Secondary Education, 2009)
In article process of performance of qualifying work is considered, motives and methods of creation of a picturesque composition are analyzed.